Pendayagunaan Alat Peraga Dalam Pembelajaran Tematik Di SDN 3 Mojorebo Wirosari Grobogan - Astutik, Sri, Prof. Dr. Abdul Ngalim, M.M, M.Hum, Dr. Sumardi, M.Si (2016)
Sri Astutik. Q.100.140.025. Reforms in Learning Thematic Viewer tool at SDN 3 Mojorebo Wirosari Grobogan. Thesis. Graduate program. Muhammadiyah University of Surakarta. 2015. The purpose of this study was to describe the thematic learning materials science with the use of props media images in SDN 3 Mojorebo Wirosari Grobogan. To describe the interaction of students in science thematic learning with the use of props media images in SDN 3 Mojorebo Wirosari Grobogan. To describe the IPA thematic learning activities with the use of props media images in SDN 3 Mojorebo Wirosari Grobogan. This research is a type of research approach used in this study is a qualitative approach (qualitative research). Takes place at SDN 3 Mojorebo Wirosari Grobogan. Methods of data collection using in-depth interviews, participatory observation, and documentation. Data analysis starting from (1) data collection, (2) data reduction, (3) display the data, and (4) conclusion. Test the validity of the data using the credibility, tranferabilitas, confirmability and dependability. Results of this study are (1) Learning materials are prepared based on themes by models cobwebs. The more precise preparation of learning materials, students more easily understand the material provided so that the learning objectives achieved well. Emphasis on media image in science subjects. (2) The interaction of learning established through models and learning methods are used. More varied teaching methods used, the interaction that exists more effective learning so that learning is not centered on the teacher and students can play an active role in learning. (3) Student learning activities carried out in the classroom and outside the classroom. The more frequently teachers use outside the classroom environment as a source of learning, student learning activities more meaningful so that students not only understand the material well but also be able to apply it in everyday life.